Comparison of pulmonary artery dimensions in swine obtained from catheter angiography, multi-slice computed tomography, 3D-rotational angiography and phase-contrast magnetic resonance angiography - Pewowaruk, Ryan (Int J Cardiovasc Imaging, 2020)
Accurate pulmonary artery (PA) imaging is necessary for management of patients with complex congenital heart disease (CHD). The ability of newer imaging modalities such as 3D rotational angiography (3DRA) or phase-contrast magnetic resonance angiography (PC-MRA) to measure PA diameters has not been compared to established angiography techniques. Measurements of PA diameters (including PA stenosis and PA stents) from 3DRA and non-contrast-enhanced PC-MRA were compared to 2D catheter angiography (CA) and multi-slice computed tomography (MSCT) in a swine CHD model (n = 18). For all PA segments 3DRA had excellent agreement with CA and MSCT (ICC = 0.94[0.91–0.95] and 0.92[0.89–0.94]). 3DRA PA stenosis measures were similar to CA and MSCT and 3DRA was on average within 5% of 10.8 ± 1.3 mm PA stent diameters from CA and MSCT. For compliant PA segments, 3DRA was on average 3–12% less than CA (p < 0.05) and MSCT (p < 0.01) for 6–14 mm vessels. PC-MRA could not reliably visualize stents and distal PA vessels and only identified 34% of all assigned measurement sites. For measured PA segments, PC-MRA had good agreement to CA and MSCT (ICC = 0.87[0.77–0.92] and 0.83[0.72–0.90]) but PC-MRA overestimated stenosis diameters and underestimated compliant PA diameters. Excellent CA-MSCT PA diameter agreement (ICC = 0.95[0.93–0.96]) confirmed previous data in CHD patients. There was little bias in PA measurements between 3DRA, CA and MSCT in stenotic and stented PAs but 3DRA underestimates measurements of compliant PA regions. Accurate PC-MRA imaging was limited to unstented proximal PA anatomy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10554-020-02043-9) contains supplementary material, which is available to authorized users.